212k views
5 votes
An equation is shown below: 6x + 2x + 13 = 3x ? 12 Part A: Write the steps you will use to solve the equation. (4 points) Part B: What value of x makes the equation true? (1 points)

User JSC
by
5.2k points

2 Answers

4 votes

Answer:

Part A

Add Like terms

6x + 2x + 13 = 3x - 12

8x + 13 = 3x - 12

get x on the left side

5x + 13 = -12

Subtract 13 from both sides

5x = -13 -12

5x = -25

Divide both sides by 5

x = -5

Explanation:


User Hugh
by
5.8k points
7 votes

Answer:

x = -5

Explanation:

6x + 2x + 13 = 3x-12

Combine like terms

8x+13 = 3x-12

Subtract 8x from each side

8x-8x+13 = 3x-8x-12

13 = -5x-12

Add 12 to each side

13+12=-5x-12+12

25 = -5x

Divide by -5

25/-5 = -5x/-5

-5 =x

User Matthijs Hollemans
by
5.5k points